Comprehensive Analysis of Aquaporin Superfamily in Lung Adenocarcinoma - Lin, Guofu; Chen, Luyang; Lin, Lanlan; Lin, Hai; Guo, Zhifeng; Xu, Yingxuan; Hu, Chanchan; Fu, Jinglan; Lin, Qinhui; Chen, Wenhan; Zeng, Yiming; Xu, Yuan (Frontiers in Molecular Biosciences, 2021)
Background: Lung adenocarcinoma (LUAD) is the most common subtype of lung cancer with an increasing morbidity and mortality. Previous studies have demonstrated that aquaporins (AQPs) family members were correlated with tumor progression and metastasis in several kinds of malignancies. However, their biological behaviors and prognostic values in LUAD have not been comprehensively elucidated. Methods: RNA sequencing and real-time polymerase chain reaction (RT-PCR) were used to assess AQP1/3/4/5 genes expressions in LUAD patients using GEPIA, UALCAN database. And then, Kaplan-Meier analysis, cBioPortal, GeneMANIA, Metascape, TISIDB and TIMER were utilized to determine the prognostic value, genetic alteration and immune cell inﬁltration of AQPs family members in LUAD. Results: We found that AQP3 expression was significantly elevated and AQP1 expression was obviously reduced in LUAD patients, whereas the expression levels of AQP4 and AQP5 exhibited no significant changes. The Kaplan–Meier survival analysis indicated that the higher expressions of AQP1/4/5 were related to longer overall survival (OS). Of interest, AQP3 was significantly correlated with the clinical tumor stage and lower AQP3 expression showed favorable prognosis in LUAD patients, which suggested that AQP3 may be a potential prognostic biomarker for the survival of patients. Through functional enrichment analysis, the functions of these four AQPs genes were mainly involved in the passive transport by aquaporins, water homeostasis and protein tetramerization. Moreover, AQP1/3/4/5 expression were strongly associated with tumor-infiltrating lymphocytes (TILs) in LUAD. Conclusion: AQP3 can be used as a prognosis and survival biomarker for LUAD. These findings may provide novel insights into developing molecular targeted therapies in LUAD.